Framework for the Assessment of Benefits of Action or Cost of Inaction for Drought Preparedness - Venton, Paul (World Bank, Washington, DC, 2019)
This working paper draws from the joint World Bank and World Meteorological Organization / Global Water Partnership Integrated Drought Management Program (IDMP) work stream on benefits of action and costs of inaction (BACI) for drought preparedness and mitigation. It suggests a methodological framework for assessment of BACI as a tool to support a shift in drought policy and programs from crisis management to a risk management approach. The framework should be systematic enough to allow for comparability across countries and contexts, with the option of being tailored to the context in which it is being used. In proposing an initial framework for BACI analysis, the authors use the ten-step methodology for developing drought strategies that was created by Wilhite et al. and subsequently codified by IDMP to help organize the assessment. In this way, the authors embed the BACI assessment in the overall development of a drought risk management strategy. This document is a first approach to guide those responsible for drought management and BACI assessments to ask the right questions at the different stages. Key next steps are to experiment with this draft approach by applying it in multiple contexts to test its usability and to develop more case study examples to showcase how this process can be undertaken and how it can be advantageous to stimulate positive action.